FRI0169 Intravenous golimumab is effective in patients with active rheumatoid arthritis despite methotrexate therapy with results observed by 2 weeks: Results of the phase 3, multicenter, double-blind, placebo-controlled trial. (23rd January 2014) - Weinblatt, M.E.; Bingham, C.O.; Mendelsohn, A.M.; Kim, L.; Mack, M.; Lu, J.; Baker, D.; Westhovens, R.
Abstract : Objectives: To evaluate the efficacy of IV GLM 2mg/kg+MTX in pts with active RA despite MTX. Methods: Pts (n=592) with active RA (≥6/66 swollen joints, ≥6/68 tender joints, CRP≥1.0mg/dL, rheumatoid factor and/or anti-CCP antibodies positive at screening) despite ≥3mo of MTX (15-25mg/wk) participated in this multicenter, randomized, double-blind, placebo (PBO)-controlled phase 3 study. Pts were randomized to IV GLM 2mg/kg or PBO at wks0&4 and q8wks; all pts continued their stable MTX. Pts randomized to PBO with <10% improvement in combined swollen & tender joint counts at wk16 could early escape to IV GLM 2mg/kg (wks16&20, q8wks). Primary study endpoint was ACR20 at wk14. Responses are reported using a non-responder imputation, with LOCF for continuous variables. Results: Baseline demographic and disease characteristics were comparable between grps (80.4% Caucasian, 81.6% female, median age 52yrs, median weight 69.6kg, median swollen joint/tender joint counts 12.0/23.0, median CRP 1.9mg/dL, median DAS28-CRP 5.9, median HAQ 1.625). Baseline mean CDAI scores were 38.5 and 38.4 and baseline mean SDAI scores were 41.3 and 40.6, for GLM+MTX and PBO+MTX grps, resp. 96% of pts (570/592) completed the 24wk study period; 4% (22/592) of pts discontinued, mostly due to AE (2.3%, GLM+MTX and 1.0, PBO+MTX). 34.5% of pts in the PBO+MTX grp entered early escape and initiated GLM at wk16 and were considered non-responders in subsequent analyses. At wk14, significantly (p<0.001) larger proportions of pts receiving GLM+MTX vs PBO+MTX achieved ACR20 (59% vs 25%, resp), DAS28-CRP good/moderate response (81% vs 40%, resp), ACR50 and a greater median improvement in HAQ score (0.500 vs 0.125, resp), all of which were also significantly improved vs PBO at wk2 (wk2 assessments not corrected for multiplicity). In post-hoc analysis, significant improvements were seen in CDAI and SDAI measurements at wk14 (p<0.001). At wk14, consistent treatment effects for ACR20 were observed across subgroup analyses. Similar proportions of pts receiving GLM+MTX and PBO+MTX reported AE through wk16 (47% and 44%) and wk24 (53% and 49%). Through wk24, serious AEs, most commonly serious infections, were reported by more GLM+MTX (4% and 1%, resp) than PBO+MTX (2% and 0%, resp) pts. No cases of TB or serious opportunistic infections were reported. 1 pt in PBO+MTX group died (presumed stroke). Through wk24, proportion of infusions with infusion reactions and pts with infusion reactions were 1.1% vs. 0.2% and 3.5% vs 0.5% in the GLM+MTX and PBO+MTX grps, resp. There were no serious infusion reactions. Conclusions: IV GLM+MTX significantly improved RA signs and symptoms in pts with active RA despite ongoing MTX, in some cases within 2 wks. Disclosure of Interest: M. Weinblatt Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, C. Bingham III Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study, A. Mendelsohn Employee of: Janssen Research & Development, LLC, L. Kim Employee of: Janssen Research & Development, LLC, M. Mack Employee of: Janssen Research & Development, LLC, J. Lu Employee of: Janssen Research & Development, LLC, D. Baker Employee of: Janssen Research & Development, LLC, R. Westhovens Grant/Research support from: Investigators for Janssen Research & Development, LLC sponsored clinical study